Estudio del contenido nutricional de la lonchera del programa de alimentación escolar del ministerio de educación en niños de la escuela dra. June guzmán serrano de la ciudad de Quevedo. Noviembre 2023 - abril 2024. - Bajaña Garces, Johnny Alexander (2024)
The present research was about the study of the nutritional content of the school lunchbox of the school feeding program of the Ministry of Education in children of the Dr. June Guzmán Serrano School in the city of Quevedo, which aims to determine the acceptance and nutritional content of the school lunchbox of the school feeding program in children from 4 to 6 years old. In addition to identifying the foods contained in the school lunch box, establishing the acceptance of the school lunch box through a sensory acceptance test and analyzing the nutritional content of the food according to the nutritional requirements of the age group and current regulations. A descriptive research methodology was applied, seeking to obtain nutritional information through the analysis of the data collected, i.e. macronutrients and micronutrients that have greater relevance when acquiring non-communicable diseases such as overweight, obesity, hypertension, diabetes, among others. The non-experimental, cross-sectional research design allowed the data collected through the surveys to be carried out during the research period.